Influence of Cr2O3 on highly nonlinear properties and low leakage current of ZnO–Bi2O3 varistor ceramics. Issue 9 (July 2016) - Bai, Hairui; Li, Shuhui; Zhao, Yunhan; Xu, Zhijun; Chu, Ruiqing; Hao, Jigong; Chen, Chong; Li, Huaiyong; Gong, Yunyun; Li, Guorong
Abstract: ZnO–Bi2 O3 –Sb2 O3 –Co2 O3 –MnO2 – x Cr2 O3 (ZBSCM– x Cr2 O3, 0≤ x ≤0.6 mol%) varistors were fabricated through the conventional solid state method, and the effects of Cr2 O3 on the microstructures and electrical properties were investigated. Results showed that the secondary phases CrBi18 O30 and Co2 Cr0.5 Sb0.5 O4 emerged when x ranges from 0.2 to 0.4. In these compositions, Cr2 O3 acted as a donor and decreased the electrical properties of ZBSCM. For samples with x =0.5, the secondary phases transformed to MnCr2 O4 and the electrical properties increased significantly: the nonlinear coefficient α sharply increased up to 80.71 and the barrier height ϕ b reached 3.88 eV. This indicates that the donor effect of Cr2 O3 disappeared. In addition, with the increase of Cr2 O3, the average grain size of ZnO decreased from 7.48 μm to 5.46 μm, which in turn resulted in an increase of breakdown voltage E 1mA from 216.17 V/mm to 362.50 V/mm. Besides, all the samples showed the low value of leakage current of lower than 0.1 μA. This varistor might be a promising candidate for highly effective applications.